Effect of occupational exposure to benzene on phytohaemagglutinin (PHA) stimulated lymphocytes in man. Issue 8 (August 1988) - Yardley-Jones, A; Anderson, D; Jenkinson, P
Abstract : This study was carried out to investigate the effects of potential low level exposure to benzene on phytohaemagglutinin (PHA) stimulated lymphocytes. Sixty six male workers of a refinery population were studied and compared with 33 control workers in the same refinery who were not known to have been exposed to benzene. The responsiveness of the lymphocyte to PHA as a measure of blastogenesis was measured by the incorporation of radio labelled thymidine by the stimulated lymphocytes in vitro. Questionnaires were used to determine various lifestyle factors such as smoking, drinking, and exposure to ionising radiation. The results showed that there was no difference between the exposed group (mean 28928 + 1524 SE (decays per minute (DPM] as compared with the control group (mean 28304 + 2483 SE DPM). Furthermore, it was not possible to determine any effects attributable to various social factors. There was, however, a suggestion of a decrease in mitogenic response with age in both exposed and control workers that was consistent with other studies. It has been shown that products of benzene metabolism may affect the mitogenic response of lymphocytes in a similar way to known promoting agents. This study was unable to show these effects, probably as a result of the low exposures encountered by the individuals.